2022
DOI: 10.3389/fpsyt.2022.814676
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Psychological Impacts of COVID-19 and Loneliness in Patients With Dementia: A Cross-Sectional Study From Iran

Abstract: ObjectivesAlthough the COVID-19 pandemic has affected people all around the world, the elderly is at a higher risk of suffering from its consequences. One of the serious concerns is developing loneliness and post-traumatic stress symptoms, which may contribute to cognitive decline at older ages. This study aimed to examine the psychological responses and loneliness in elderly patients diagnosed with dementia.MethodsTwenty-one patients diagnosed with dementia, with ages older than 40, and 19 caregivers were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In addition, it aligns with the studies that showed younger age groups, in particular, experienced a higher prevalence of loneliness during COVID-19 lockdowns ( 27 , 28 ). These findings are noteworthy, considering that social isolation as results of social distancing during pandemics might trigger mental health concerns ( 29 , 30 ), including general psychological distress ( 31 ), decreased well-being ( 32 ), and lower life satisfaction ( 32 ). In contrast, those positively affected by social-networking activities were significantly less likely to feel depressed or anxious, maintain or decrease stress, and increase or maintain their quality of life.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, it aligns with the studies that showed younger age groups, in particular, experienced a higher prevalence of loneliness during COVID-19 lockdowns ( 27 , 28 ). These findings are noteworthy, considering that social isolation as results of social distancing during pandemics might trigger mental health concerns ( 29 , 30 ), including general psychological distress ( 31 ), decreased well-being ( 32 ), and lower life satisfaction ( 32 ). In contrast, those positively affected by social-networking activities were significantly less likely to feel depressed or anxious, maintain or decrease stress, and increase or maintain their quality of life.…”
Section: Discussionmentioning
confidence: 94%